Pemanfaatan Tenaga Surya Dan Iot Untuk Menjaga Kualitas Air Dalam Budidaya Ikan Berbasis Web - Paulo F De J. Martins; Gigih Priyandoko; Mohammad Mukhsim; Sumartono Ali Putra (Jurnal FORTECH, 2025)
Water turbidity is a critical factor affecting fish growth and health in aquaculture, thus requiring an efficient and automated water quality monitoring system. This study developed an Internet of Things -based system powered by solar energy to monitor and control water quality in real-time. The system uses an ESP32 microcontroller integrated with turbidity, pH, and temperature sensors, as well as water level control, automatic feeder, and an INA219 power monitoring module. Sensor data is transmitted via Wi-Fi to a Firebase-based web dashboard. When turbidity exceeds 25 NTU or pH falls outside the 6.5–8.5 range, the system automatically activates a solenoid valve to discharge dirty water, runs a pump to refill clean water, and injects a pH balancing solution, while sending notifications to the user. Test results show an average response time of 2–3 seconds, with sensor accuracy of ±0.2 for pH, ±0.5°C for temperature, and ±5 NTU for turbidity. The system demonstrates high energy efficiency, consuming approximately 12.6 Watts, with solar panel voltage maintained between 12.9–13.5 Volts, and battery capacity stable at 87–95%. Data transmission is stable, with synchronization to the server occurring in less than 1 second. With reliable performance, quick responsiveness, and energy efficiency, this system proves to be effective in supporting sustainable fish farming, especially in areas with limited access to conventional electricity.